Study of Correlation of Serum Cholinesterase Level with Peradeniya Organophosphorus Poisoning Scale in Organophosphorus Poisoning - Gurung, Dhiraj (Journal of Karnali Academy of Health Sciences, 2021)
Background- Organophosphorus compound poisoning is a common problem in Nepal. In rural areas, cholinesterase levels are not readily available and other clinical severity scores would be useful. Peradeniya Organophosphorus Poisoning (POP) scale is a clinical severity score that has shown promise as a prognostication tool.Method- This was a single center, prospective study conducted in Nepal medical college between August 2012 to August 2014. A total of 62 cases of organophosphorus poisoning was included on the basis of history of organophosphate compound ingestion. Spearman correalation method was used to find the correlation between serum cholinesterase severity and POP scale severity.Result- Majority of the patients were between the ages of 15 to 45 and female. The most consistent clinical finding was miosis followed by altered sensorium. The most common organophosphate compound ingested was methyl parathion. No significant correlation was seen between serum cholinesterase severity and POP scale severity.Conclusion- POP scale severity does not correlate with cholinesterase level severity. Multi-center trial with larger sample size is needed due to inconsistent results amongst similar studies